The Response of the Current Account to Terms of Trade Shocks : Persistence Matters - Cashin, Paul (IMF Working Papers; Working Paper, 2003)
Is the relationship between the current account balance and the terms of trade affected by the persistence of terms of trade shocks? In intertemporal models of the current account that incorporate a consumption-smoothing and an investment response to shocks, the effect of the terms of trade on external balances is predicted to be dependent on the duration of terms of trade shocks. Using a median-unbiased estimator, an unbiased model-selection rule, and terms of trade data for 128 countries over the period 1960-99 we identify two groups of countries-those that typically experience temporary terms of trade shocks and those that typically experience permanent terms of trade shocks. The results from panel-data regressions of the two groups of countries support the theoretical predictions of the intertemporal approach to the current account. We find that the greater (lesser) the persistence of the terms of trade shock, the more (less) the investment effect dominates the consumption-smoothing effect on saving, so that the current account balance moves in the opposite (same) direction as that of the shock.